Analisis Pengelolaan Sampah Rumah Tangga di Permukiman Sekitar Daerah Aliran Sungai (DAS) Desa Ibul Besar II - Zhafirah, Yunida; Ardillah, Yustini; Oktivaningrum, Rafika; Pratiwi, Laura Dwi (Poltekkes Kemenkes Tanjung Karang, 2024)
The problem of household waste in Ogan Ilir Regency is increasingly complex due to the characteristics of the wetland area. Poor management of household waste around the watershed can cause various problems, both environmental and public health issues. This study analyzes household management in settlements around the Ibul Besar II Village watershed. This study is qualitative. The informants in this study consisted of seven key informants and five ordinary informants who were selected using the purposive sampling method. Data was collected through in-depth interviews, observation, and documentation (photovoice). The study results show that efforts to eliminate household waste still need to be improved. Four out of six housewives reuse used buckets. However, only two out of six housewives recycle. Household waste is not sorted into five types. The collection and transportation of household waste do not meet the requirements due to the unavailability of TPS or TPS 3R, waste carts, and limited waste transportation. The household waste is burned, and the waste is not processed. It can be concluded that household waste management in settlements around the Ibul Besar II Village watershed has not gone well. Waste reduction efforts are still limited, and waste handling needs to be corrected. Household waste management in Ibul Besar II Village experiences many obstacles, such as economic limitations, time, facilities, and infrastructure, and lack of public awareness and knowledge about the stages of good and correct household waste management.